Developing conceptual governance model for collaborative knowledge management system in public sector organisations - Ali, Azlina; Nor, Rozi Nor Haizan; Abdullah, Rusli; Azmi Murad, Masrah Azrifah (Universiti Utara Malaysia Press, 2016)
Nowadays most of the public sector organisations are implementing a knowledge management system (KMS) to assist the systematic creation and sharing of their knowledge resources. The recent technological needs, collaboration and cooperation among public sector organisations (PSO) serve a vital role in the development of knowledge management systems (KMS). However, in order to establish a successful and standardised collaborative KMS amongst Malaysian PSO (MPSO), proper governance needs to be in place. The aim of this study is to identify governance components for collaborative KMS (CKMS). Accordingly, the journal articles published within the period 1998-2013 were identified and analysed. The articles were sourced mainly from Knowledge Management Research & Practice, Science Direct, Emerald, MIS Quarterly, as well as from some other academic databases. Keywords used during the literature search were “governance”, “knowledge management system”, “collaboration”, “collaborative knowledge management system”, “knowledge sharing” and “knowledge management governance”. Moreover, expert opinion from the public sector expert teams and academic experts was also acquired from several consultation sessions to ensure that the components obtained from the readings meet the requirements of KMS collaborations. Based on the analysis and consultation, a conceptual model for governance of CKMS is constructed.